Mechanical ventilation in patients diagnosed with COVID -19 - Adisnay Rodríguez Plasencia; Jennifer Lisette Miranda Miranda; Rider Fabiàn Donoso Noroña; Elisabeth Germania Vilema Vizuete (Medisur)
Foundation: mechanical ventilation is any artificial respiration procedure that uses a mechanical device to help supply the ventilatory and oxygenation function. Prone position ventilation has been shown to improve oxygenation and lung mechanics in patients with acute respiratory distress syndrome. Objective: to describe the characteristics of mechanical ventilation in patients diagnosed with COVID -19 at the Ambato General Hospital. Methods: descriptive, cross-sectional study carried out at the Ambato General Hospital, Ecuador, from October 2021 to May 2022. A population of 176 patients who were treated in the Intensive Care Unit and who met the following inclusion criteria: connected patients to mechanical ventilation and that the doctor in charge agreed to include them in the research were analyzed. Results: more than half of those treated belong to the male gender; 55.1% are between 35 and 49 years old and obesity predominated among the risk factors with 42.1%. When distributing the patients according to the type of ventilation and gender, there was a male gender predominance, both in non-invasive, invasive and spontaneous mechanical ventilation. Conclusions: adopting appropriate therapeutic measures, such as mechanical ventilation, to treat serious diseases improves the patients’ prognosis and survival.